Salafiyah Dayah's Strategy in Producing Quality Students in the Modern Era - Munzir; Lubis, Lahmuddin; Arsyad, Junaidi (JTP - Jurnal Teknologi Pendidikan, 2024)
This study aims to analyze the strategies implemented by Salafiah Islamic boarding schools in producing quality students in the modern era, as well as analyzing the supporting and inhibiting factors that influence the process. Salafiah Islamic boarding schools, as traditional Islamic educational institutions, have an important role in producing students as future ulama who are able to answer the challenges of the times. This study uses a qualitative method with a phenomenological approach. Data were collected through document studies, observations and in-depth interviews. The results of the study indicate that Salafiah Islamic boarding schools have adapted their educational strategies to be relevant to the demands of the modern era. Several strategies found involve the implementation of a curriculum that combines religious knowledge with the use of technology in the learning process, as well as increasing community involvement in supporting education at the Islamic boarding school. Supporting factors in producing ulama cadres at Salafiah Islamic boarding schools involve management commitment, community support, and technology integration. Meanwhile, inhibiting factors include limited resources, socio-cultural changes, and resistance to change among traditionalists. This study provides a deeper understanding of the dynamics of education at Salafiah Islamic boarding schools, as well as providing recommendations to improve the effectiveness of educational strategies in producing ulama cadres who are able to compete and make positive contributions in modern society.